2015
DOI: 10.3906/sag-1403-80
|View full text |Cite
|
Sign up to set email alerts
|

Forensic medicine evaluation of Alzheimer patients: a series from Ankara, Turkey

Abstract: Background/aim: Pathophysiological changes due to Alzheimer disease and increasing age might result in situations requiring forensic evaluation in the elderly. Judicial bodies might need forensic evaluation of trauma and the decision-making capacity of Alzheimer patients. This study aimed to determine the demographic and clinical characteristics of Alzheimer patients seen for forensic evaluation.Materials and methods: Forensic records issued by the Department of Forensic Medicine of Hacettepe University in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…4 Psychological and mental evaluation abilities of older people get disrupted due to dementia processes and multiple chronic diseases. 5 In our study, we found that the most frequent reason for non-traumatic forensic admission was poisoning. CO is seen as the most frequent poisoning factor with a rate of 9.69%, and we believe that the most probable reason for this result is that older patients are incapable of sensing danger or protecting themselves from danger.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…4 Psychological and mental evaluation abilities of older people get disrupted due to dementia processes and multiple chronic diseases. 5 In our study, we found that the most frequent reason for non-traumatic forensic admission was poisoning. CO is seen as the most frequent poisoning factor with a rate of 9.69%, and we believe that the most probable reason for this result is that older patients are incapable of sensing danger or protecting themselves from danger.…”
Section: Discussionmentioning
confidence: 54%
“…4 Although forensic cases can be observed in all age groups, both physical and mental disabilities increase the possibility of exposure in the ageing population. 2,5 Slowing of the mental processes and decline of the extremity coordination contributes to occurrence of trauma, whereas the decrease of self-care related to physical and psychological limitations and inability to protect oneself can prepare the ground for abuse and poisoning. [6][7][8] Moreover, comorbid diseases and decline in the physiological reserves in older population make the reflections of forensic processes on this patient group more complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation